The effect of fumaric acid-sodium bicarbonate on the green tea effervescent granule’s quality made by dry granulation - Agatha Budi Susiani Lestari; Maria Yuli Trisusilawati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Tea plant (Camellia sinensis L.) had been known contains epigallocathecin gallate (EGCG) that can be used to maintain the healthy. In this research, the green tea will be tried to be formulated in effervescent dosage form, with the focus on the effect among fumaric acid, sodium bicarbonate, or the interaction between fumaric acid and sodium bicarbonate on the green tea extract effervescent granule’s physical properties, that made by dry granulation method. Physical properties of effervescent granule that been study were moisture content, flow rate, disintegration time, and pH of the solution. The result showed that sodium bicarbonate was dominant in determining pH, granule flow rate and moisture content of granule, whereas fumaric acid dominant in disintegration time of effervescent granule.Key words: green tea, fumaric acid, effervescent granule, dry granulation